UNIDADE DEMONSTRATIVA DE COMPOSTAGEM - ALVES, Jonilda da Silva; MORAIS, Glaucia Almeida; LIMA, José Vitor Nobrega de; FREITAS, Letícia da Silva; CAETANO, Luan Otávio Fernandes; SILVA, Vitória Aires (ANAIS DO ENIC, 2023)
-